EFEKTIVITAS PEMBERIAN SUSU KEDELAI DALAM MENGATASI KELUHAN PADA MASA PRE MENOPOUSE DI KLINIK BIDAN MAIHARTI KISARAN BARAT TAHUN 2020 - Nikmah Jalilah Ritonga; Yuni Sartika Limbong; Riris Sitorus; Diah Evawanna Anuhgerah (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2021)
ABSTRAK Pre menopause is a physiological condition characterized by irregular menstruation. Symptoms that often arise such as hot flush, night sweats, restlessness, easy fatigue, pain during intercourse. Overcoming complaints of pre-menopausal non-pharmacological can be done with soy milk. The purpose of this study was to determine the effectiveness of soymilk in dealing with pre-menopausal complaints at the Midwife Maiharti Clinic, West Range 2020. This study used a quantitative method, with a quasi-experimental design with a control time series design. The study population was pre-menopausal mothers who experienced pre-menopausal symptoms at the Midwife Maiharti Clinic, West Range. The sample selection used purposive sampling as many as 18 people, 9 people were given intervention and 9 people as controls. The results of the study using Wilcoxon sign rank test obtained results for groups that were given pre and post p-value interventions 0.002 <0.05. The results of the study using Wilcoxon sign rank test obtained results for the control p-value 0.009 <0.05. The conclusion is that there are differences in the two groups after being given soy milk in dealing with pre-menopausal complaints